Corelation Study Between Knowledge, Attitude Toward Tenaager’s Sexual Beahaviour Who Was Domiciled In English Village - Sodik, Muhammad Ali; Mayta Sari D; Saheri, Moh. (Journal of Global Research in Public Health, 2019)
Youth is a great potential for nation progressed. However, if it’s not properly nurtured or left alone, adolescents may develop in a negative direction, and will become a burden for the state. While the current conditions, according to the results of the RPJMN indicator survey in 2012, many teenagers who have been dating and behaving courtship excess. As a result, it leads to unwanted pregnancies and ultimately performs unsafe abortion acts because the teenage couple are not yet ready to build a family. this study research is to know the correlation between knowledge and attitude toward sexual behaviour of teenagers who are domiciled in several of dormitories in Anyelir Street of English Village Pare-Kediri. In this study research method uses cross-sectional. This study research was conducted in several dormitories in Anyelir Street of English Village Pare-Kediri. With total samples were 149 teenagers who have fulfilled the criteria. For data analysis uses multiple linear regression statistic test. this study research can be assumed that from 149 teenagers there were 70 or 47% of teenagers had sufficient knowledge, while, the attitudes can be elucidated that from 149 teenagers were 79 or 53% of teenagers had sufficient attitudes, whereas the behaviour can be elucidated that from 149 teens were 120 or 80.5% Never had intercourse. Based on this study research result of statistic test by multiple linear regression, it is known that the sig value. F = 0,000 <α 0.05, so, the hypothesis accepted which means there is a correlation between knowledge, attitudes toward teenager’s sexual behaviour that domiciled in several of dormitories in Anyelir Street of English Village Pare-Kediri. Behaviour has closed relation to knowledge and attitude because by good knowledge premarital sex can avoid negative attitude toward the opposite sex so it can control teen’s libido such as kissing, hugging then to reduce the risk of pregnant before marriage and it can cause infectious disease by intercourse before marriage. .